Pathogenicity of P. terrestris on Maize Seedlings - LEVIĆ, JELENA (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Pathogenicity of P. terrestris was determined by the Knop's medium slants method in test tubes. Isolates originated from the roots of maize (Zea mays L.), barley (Hordeum vulgare L.), Johnson grass (Sorghum halepense Pers.), sorghum (Sorghum bicolour (L.) Moench.), garlic (Allium sativum L.), onion (Allium cepa L.), barnyard millet (Echinochloa crus-galli (L.) P.Beauv.) and green foxtail (Setaria viridis (L.) P.B.). A fragment of a fungal colony, cultivated on PDA, was placed on the bottom of Knop's medium slant in each test tube and then sterilised maize seeds were placed 2 cm away from the inoculum. After 21-day inoculation of seeds, the intensity of the development of symptoms on maize seedlings was estimated. The reddish or dark pigment on the root, mesocotyl and/or coleoptyl of seedlings was an indicator for the infection by the fungus under in vitro conditions. Based on the pathogenicity test, the isolates were classified into the following three groups: slightly (3 isolates), moderately (6 isolates) and very pathogenic (6 isolates) to maize seedlings. The obtained results show that P. terrestris, originating from different hosts, can be a maize pathogen. These results can explain the high frequency and high incidence of this fungus on maize roots in Serbia.